pengaruh brand trust dan brand loyalty pada keputusan pembelian sepatu merek adidas di Bandar Lampung - Cahyani Pratisti; Niken Paramitasari (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
The study aims to determine the effect of 1) Brand trust, 2) Brand loyalty on Adidas Purchase decision in Bandar Lampung. The quantitative associative research used multiple regression found that brand trust and brand loyalty effected Adidas purchase decision. So, brand trust and brand loyalty lead to certain marketing advantages including reducing marketing costs, attract new consumers, provide superior trading leverage, performing favorable word of mouth, and resist competitor marketing efforts. Keywords: Brand trust, Brand loyalty, Purchase decision